MOLECULAR IDENTIFICATION OF ROOT-KNOT NEMATODES MELOIDOGYNE SPP. ISOLATED FROM CUCUMBER FARMS IN DIFFERENT IRAQI REGIONS - M. R. Abbas; S. M. K. Saadedin; A. A. Suleiman (مجلة الأنبار للعلوم الزراعية)
Meloidogyne spp. is one of the most common crop diseases globally. Due to the similarity in morphological features between various Meloidogyne spp., molecular techniques were used to identify their species. In this study, conducted in October 2022 and January 2023, genetic identification was undertaken on 61 samples collected from nine distinct regions of Iraq. PCR was used to amplify the part of the Meloidogyne spp. genome between the COI and 16S mtDNA genes. Afterward, M. incognita, M. hapla, M. javanica, M. enterolobii, and M. arenaria were genotyped using Sequence Characterized Amplified Region (SCAR-PCR), with decreasing prevalence rates, respectively. The data revealed that the 50 isolates of M. incognita were in the Shuan Kara region, which means they exhibited the highest percentage. Interestingly, M. arenaria was the least common species in all areas and was isolated from Ghanaia. Additionally, M. enterolobii's representation of other species led to the discovery of a new one in Iraq. The coexistence of more than two species within a single region has never been documented. The goal of this study is to use molecular detection to find out how different Meloidogyne species infect cucumber plants and how important it is to be able to spot infected regions.